Study of Virtual Reality and IoT for Exploring the Deep Sea - Yuan-Hsun Liao; Hsiao-Hui Li; Zong-Han Xie (Journal of ICT, Design, Engineering and Technological Science, 2019)
In the deep sea, many puzzles have not been solved. We must overcome many difficulties if we want to explore the deep sea. Un- predictable dangers may occur when humans carry out deep-sea exploration. At this time, we can take advantage of Virtual Reality (VR) and the Internet of Things (IoT) characteristics. This paper studies the combination of the IoT and VR that can connect items to the internet, control items and send back data to observe the condition of the equipment and water pressure and break through the space constraints to let people explore the deep sea even in the virtual world. This design will greatly reduce the probability of danger. And the user can achieve the purpose of deep-sea exploration. The ocean is an area that humans have not yet fully developed, and it is also full of mystery and danger. But using VR, you can avoid temperature differences, water pressure and dangerous creatures in the sea. Through VR, you can add new things so that things that can't usually happen in real life can be presented in a virtual way.